Epidemiology of Hepatitis E in Low- and Middle-Income Countries of Asia and Africa - Kmush, Brittany; Wierzba, Thomas; Krain, Lisa; Nelson, Kenrad; Labrique, Alain B. (Seminars in Liver Disease, 2013)
Hepatitis E is an acute, viral hepatitis primarily transmitted through the fecal–oral route. The first major epidemic of hepatitis E virus (HEV) was reported in 1955 in Delhi, India. Since that time, numerous epidemics have been reported across the low- and middle-income countries in Asia and Africa. Even in the absence of large-scale outbreaks, hepatitis E is an important cause of clinical hepatitis. Serologic studies across Asia and Africa show a high prevalence of anti-HEV antibodies. Interest in hepatitis E has increased over the last two decades. However, there are many unanswered questions about the epidemiology of hepatitis E, including a low clinical illness rate in children and the high case fatality rate in pregnant women. Widespread usage of a hepatitis E vaccine may serve to relieve the burden of HEV disease in low- and middle-income countries in Africa and Asia.
Keywords: hepatitis E; HEV; Asia; LMIC; Africa